Principles for mainstreaming gender equality in the South African rural water services sector - Rust, Urszula Anna (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.